Inactivity is an independent health risk : objectively measured muscle activity and inactivity during normal daily life of ordinary people - Pesola, Arto (2011)
Pesola, Arto 2011. Inactivity is an independent health risk: objectively measured muscle activity and inactivity during normal daily life of ordinary people. Master’s thesis in exercise physiology. Department of Biology of Physical Activity, University of Jyväskylä. 96 pages.